Influence of timber grain distribution on orientation of saw cuts during application: Reference to heritage structures in Sri Lanka. (December 2019) - Mendis, M.S.; Halwatura, R.U.; Somadeva, D.R.K.; Jayasinghe, R.A.; Gunawardana, M.
Abstract: Longitudinal arrangement of wood fibers is known as wood grains. It is one of the most important physical aspects of timber in applications. The properties differ along the grain and against the grain. Straight grains run parallel to the longitudinal axis of the wood. Meanwhile the cross grain deviates from the longitudinal axis as spiral and diagonal grains. This orientation has a high influence on the wood and affects physical properties during application. In order to study this, a detailed analysis was performed on Ambalam structures; a cherished heritage structure originated from the vernacular architecture in Sri Lanka. These structures are existing living proofs of vibrant construction materials in an exposed environment built with in unrevealed traditional construction technologies practiced by our ancestors. Badulla Ambalama, Padivitiya Ambalama, Panavitiya Ambalama, Karagahagedra Ambalama, Giruwa Ambalama and Rukula Ambalama were selected as case studies for this research. The growth ring distribution of the exposed surfaces on the structural components were mapped using AutoCAD software. The results of mapping and overlapping the growth ring distribution of the specific timber assisted to generate clues on the size of the tree and to determine the orientation of the saw pattern from the wood log. The generated growth ring maps revealed the sensitivity and the adequate knowledge in material manipulation utilized for specific structural components respect to its load distribution by our ancestors. The Ambalam heritage structures in Sri Lanka have enlighten timber as an acceptable construction material with a respectable service life for tropical countries.